Produção e qualidade da madeira para laminação de Pinus taeda em diferentes sítios florestais - Dalgallo, Bárbara (2013)
The objective of this research was to conduct modeling Growth and Production for Pinus taeda, and sort it in forest sites and assess whether there is influence of site on wood quality. The area of study is 807ha. The stand is located in the center-south of Paraná, in Guarapuava. The data for modeling and classification of sites were obtained through installments permanent of a continuous forest inventory, with ages varying between 9 and 20 years. For analysis of the density and yield, were collected 6 trees in the three ages tested (9, 14 and 20 years). The models were evaluated using the adjusted determination coefficient, standard error of the estimate and graphical analysis of the residuals. To determine the density and dimensional stability, were made specimens in the form of wedges, according to NBR 7190. The evaluation of the efficiency of lamination was made based on the first two logs collected from each tree, with the same sampled for density and dimensional stability. Hypsometric and volumetric models that best adjusted the data were tested by Nogueira (2003b) and Schumacher-Hall (1933). For the site classification, the model that best fit the data was the Silva-Bailey. The density was influenced by age, but not by the forest site. Concerning to dimensional stability, there was no variation in any of the factors, age and site. The effective yield, in turn, suffered significant variation by age factor.